An In Vitro Analysis and In Vivo Trial Demonstrating the Improved Iron Bioavailability of White Beans (Phaseolus vulgaris L.) After Processing Into Pasta. (14th June 2022) - Wiesinger, Jason; Cichy, Karen; Edmister, Sara; Hooper, Sharon; Glahn, Raymond
Abstract: Objectives: The cotyledon cell wall of the common bean can be a factor in Fe bioavailability. This study evaluated the iron bioavailability of two bean varieties (white or black) either boiled (intact cell walls) or extruded into pasta formulated from heat treated bean flour as the major ingredient (100% bean flour; broken cell walls). Methods: In vitro Fe bioavailability was determined via the Caco-2 Cell Bioassay. In vivo Fe bioavailability was measured by the capacity of a bean-based or bean pasta-based diet to generate and maintain total body hemoglobin iron (Hb-Fe) during a 6 week poultry feeding trial. Results: The iron and phytate concentrations of the bean-based and bean pasta-based diets consisting of tomato paste, carrot, cabbage, milk, potato and corn oil were not significantly different. The Caco-2 cell bioassay predicted that the white bean pasta diet would have the highest Fe bioavailability, closely followed by the white bean diet. The bioassay predicted the black bean diet and the black bean pasta diet would have significantly lower Fe bioavailability. For the in vivo studies, animals fed the white bean pasta diet (broken cell walls) had significantly ( p ≤ 0.05) higher hemoglobin, Hb-Fe and hemoglobin maintenance efficiencies than animals fed a white bean, black bean or black bean pasta-based diet. Although cotyledon cells were broken, the iron bioavailability of the black bean pasta was not improved after processing into pasta. The low iron bioavailability of black beans was associated with their high concentrations of seed coat procyanidin, cinnamtannin and anthocyanidin compounds that have a negative impact on the absorption of iron. Conclusions: This study shows that white colored dry bean possesses a combination of traits that result in improved iron bioavailability after processing into pasta. The enhanced Fe bioavailability from the white bean pasta is likely due to the breakage of the cotyledon cell wall during processing, thus allowing enhanced bioaccessibility of the intracellular Fe. In the black bean pasta diet, this enhancement was not observed due to the presence of the seed coat polyphenols which interacted with the released intracellular Fe and prevented Fe absorption. Funding Sources: Funded by the United States Department of Agriculture, Agricultural Research Service.